“HALAL INVESTMENT” DALAM MEMBANGUN KEUANGAN BERKAH DAN BERKELANJUTAN - Moechamad Rafi Idzwan Maulana Al Farisi; Lina Marlina Susana (Jurnal Cakrawala Ilmiah, 2025)
Halal Investment is a wealth management acticity aimed at achieving halal and blessed profits. The Quran an Hadith provide clear guidelines on the principles of Islamic Finance, Such as the prohibition of riba, gambling, and harmful activities.This Study aims of examine the concept of investment in Islam, identify permissible types of investments, and analyze the factors influencing public interest in Islamic finance. The research findings are expected to contribute to the development of the Islamic finance market in Indonesia.